The Interaction of Lexical and Grammatical Aspects in English as a Foreign Language for Iranian Farsi Speaking Learners - Pishghadam, Reza; Ziaei, Sima (Richtmann Publishing, 2012)
This study aims to investigate the claims of Aspect Hypothesis which holds that in the past tense, perfective verbsprecede imperfective verbs, having a different pattern of acquisition based on their lexical aspect, i.e., learners initiate usingperfective past marks from the prototypical verbs which contain the achievement and accomplishment lexical aspects, while theystart using imperfective past marks from the verbs whose lexical aspects are stative and activity. In this study, ten Iranian (fromMashhad) Farsi speaking learners of English were given a film to watch and retell the story in impersonal narrative in past tense.The verbs which they applied were classified into 4 lexical aspect categories with different semantic features like telicity,durativity, and dynamicity; these categories include: state, achievement, accomplishment and activity. The results suggest thatatelic verbs like state and activity verbs were easier for the students to produce in past perfect and the atelic durative verbsactivities-were produced with higher accuracy in past imperfective.